Fomentar la exportación de barras de chocolates al mercado español, por parte de la microempresa tamy s.a - Cassagne Jiménez, Jossy Nicole (2014)
The project focuses on the export of a foodstuff produced in traditional way, with labor and raw material 100% Ecuadorian, is directed at the Spanish market which was chosen by the gastronomic culture which have about chocolate and high consumption. We present a general analysis on the study of chocolate and export of this product as a finish, noting their historical background, varieties, analysis of market and technical sheet. It will be released the growth potential which represents cocoa for our economy, the Ecuador being the largest producer of fine cocoa or scent in the world. Therefore, we must exploit this absolute advantage with which we, to not only be suppliers of raw material, but also manufacturers of high quality finished products as it is the case of chocolate, where we can distinguish ourselves by the quality of our cocoa, which boasts exquisite sensory floral, aroma and unique flavor……